(untitled) (Global Conference on Multidisciplinary Research and Innovation, 2026)
Inflammatory and degenerative rheumatic disorders represent a heterogeneous spectrum of chronic diseases marked by persistent inflammation, vascular impairment, progressive connective tissue alteration, and variable systemic involvement. Despite distinct clinical phenotypes and etiological triggers, conditions such as rheumatoid arthritis, ankylosing spondylitis, reactive arthritis, osteoarthritis, allergic vasculitis, and systemic sclerosis demonstrate overlapping biological pathways that contribute to disease onset, progression, and long-term complications.